The Cost-Cutting Reforms of Higher Education in England - Callender, Claire (International Higher Education, 2011)
The British government is introducing dramatic changes to the funding of higher education in England, including the withdrawal of most of its funding for teaching and a threefold increase in undergraduate tuition fees. These reforms herald the retreat of the federal state from financial responsibility for HE, boosting HE's private-good functions at the expense of the public-good function. Will this marketisation of British HE be at the expense of social equity and universities as public, civic, and cultural institutions?